2009
DOI: 10.1007/978-3-642-04268-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Toward Real-Time Simulation of Blood-Coil Interaction during Aneurysm Embolization

Abstract: Over the last decade, remarkable progress has been made in the field of endovascular treatment of aneurysms. Technological advances continue to enable a growing number of patients with cerebral aneurysms to be treated with a variety of endovascular strategies, essentially using detachable platinum coils. Yet, coil embolization remains a very complex medical procedure for which careful planning must be combined with advanced technical skills in order to be successful. In this paper we propose a method for compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Once seen before the embolization, it promotes compaction which is responsible for aneurysm recanalization. Blood flow patterns influence compaction [ 21 ]. Our analysis showed that the complex flow patterns are closely related to the aneurysm shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once seen before the embolization, it promotes compaction which is responsible for aneurysm recanalization. Blood flow patterns influence compaction [ 21 ]. Our analysis showed that the complex flow patterns are closely related to the aneurysm shape.…”
Section: Discussionmentioning
confidence: 99%
“…To find differences between both groups, we examined flow patterns and hemodynamic parameters in all generated models. Such investigations are relevant as compaction relates to flow patterns [ 21 ]. Thus, it can be stated that CFD served as a tool that allowed us to cover two main aspects: (1) visualizing flow hemodynamics in the vicinity of all aneurysm models and performing a qualitative and quantitative comparison of obtained flow solution data and (2) validating whether the morphometric parameters associated with recanalization, indicated by our statistical analysis, result in noticeable changes in flow hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…As the method relies on particles, the coupling with deformable model can be easily done by repulsion forces (see Figure 3). More advanced fluid models, based on Eulerian approaches, were also implemented in SOFA (see [29] for instance). The flexible structure of Sofa allows the simulation of non-mechanical phenomena such as electrical waves in cardiac electrophysiology.…”
Section: Other Physical Modelsmentioning
confidence: 99%